What does "Teaching Philosophy" mean? A case study: Professor X teaching philosophy - Mitrović, Veselin (Studies in Teaching and Education, 2025)
In higher education, teaching philosophy is a crucial tool for conducting and assessing teaching quality. Yet, there is limited focus on exploring its essence. Teaching philosophy can be interpreted as a strategy in education and pedagogy, depicting how teachers tackle the teaching process. This involves both pedagogical and educational aspects. A different perspective on teaching philosophy is to view it as the direct conveyance of philosophical knowledge from teacher to students. The qualitative study in higher education is explored by looking at Professor X social and educational background, teaching in different settings, professor’s methodology of teaching philosophy from basics as well as teacher’s broader academic work, which includes writing, research, and public presentations. The research investigates teacher’s self-reflection on philosophy and the development of a "teaching philosophy from scratch," exploring how it supports X dedication to pushing philosophy beyond conventional academic environments and a particular teaching philosophy.The findings suggest that there is a connection between teaching methods and research and publication endeavors. The outcomes extend beyond the typical association to explore the essence of the link between research and teaching. This deepens our insight into the meaning of "teaching philosophy" as a diverse process that includes teaching, writing, academic endeavors, and public contributions.
Keywords: Teaching philosophy, higher education, pedagogy, students, educational and research style